GAGASAN PAMOR KERIS PADA ELEMEN DEKORATIF DINDING LOBBY MUSEUM PUSAKA DI JAKARTA - Anna Diana Taka Putri; Augustina Ika Widyani (PROSIDING SERINA, 2021)
Globalization cause the influence of other countries to replace Indonesian cultural values. The Heirloom Museum in Jakarta is one of the museums that has a collection of Indonesian cultural relics that area still preserved with their authenticity. The interior of the Jakarta Heirloom Museum does not fulfill their role for education, recreation and preservation of their collections and their image and identity does not reflect the Jakarta Heirloom Museum itself. The most displayed collection at Jakarta Heirloom Museum is keris. This shows that keris is the identitiy of Jakarta Heirloom Museum. One of the keris elemenst are the keris prestige which is found on the blade of keris. The prestige of keris has many forms. The purpose of the design is to design decorative elements from the shape of keris prestige according to the design theme and use the right material. The method used in designing the decorative elements of the Heirloom Museum is observation or direct observation and then data analysis, drafting concepts and design decisions. The prestige of Udan Mas Keris is believed to be able to provide an easy life and give blessings to their owner so that the museum is expected to attract more visitors. The lobby of Jakarta Heirloom Museum use a wall of decorative eements from the form of the prestige of Udan Mas which is packaged dynamically, so that the identity of the Heirloom Museum can be reflected in the museum lobby.